The Direct Influence of Leadership on the Commitment of State Madrasah Aliyah Teachers in West Sumatera - ., Rinalfi; Gistituati, Nurhizrah; ., Syahril; Marsyidin, Sufyarma; ., Hadiyanto (Journal of Ecohumanism, 2025)
This study aims to examine the direct influence of leadership on the commitment of teachers at State Madrasah Aliyah in West Sumatra. The research employs a descriptive quantitative method, involving a sample of 252 teachers selected using multistage cluster stratified random sampling techniques. Data were collected through questionnaires and analyzed using descriptive statistical analysis. Prerequisite tests for the analysis included the effect of the leadership variable on the organizational commitment variable. Data analysis was conducted using SPSS software. The results indicate that there is a direct influence of leadership on organizational commitment, contributing 4.88%. This suggests that the leadership variable has a significant effect on the organizational commitment variable, with a significance level of 0.00, thus the hypothesis regarding the leadership effect on organizational commitment is accepted.